2008
DOI: 10.1245/s10434-008-0226-2
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive Surgery Plus Hyperthermic Intraperitoneal Chemotherapy Improves Survival in Selected Patients with Peritoneal Carcinomatosis from Abdominal and Pelvic Malignancies: Results of 21 Cases

Abstract: We evaluated the perioperative safety profile and efficacy of cytoreductive surgery (CRS) plus hyperthermic intraperitoneal chemotherapy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…For example, some stage III and stage IV patients with CRC underwent curative surgery plus hyperthermic intraperitoneal chemotherapy (HIPEC) but some patients did not. Our previous studies demonstrated that HIPEC could improve the OS and quality of life of patients with CRC [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…For example, some stage III and stage IV patients with CRC underwent curative surgery plus hyperthermic intraperitoneal chemotherapy (HIPEC) but some patients did not. Our previous studies demonstrated that HIPEC could improve the OS and quality of life of patients with CRC [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Since 2004, we have adopted cytoreductive surgery (CRS) and HIPEC to treat selected PC patients from gastrointestinal and gynecological malignancies [19].This report summarizes our experience in 30 CRS and HIPEC procedures for the treatment of 28 gastric PC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these data are based on a limited number of cases from national referral hospitals in Western countries, but there are very few reports from Asian countries including Japan. 16,17 Thus it is generally unclear whether the Sugarbaker procedure can be performed at nonspecialized hospitals. [18][19][20] Moreover, since PMP is a rare condition and peritonectomy is an unusual procedure, the concept of the treatment may not be widely understood.…”
Section: Introductionmentioning
confidence: 99%